2017
DOI: 10.1016/j.addbeh.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Hookah tobacco use and stressful life events in a sample of young non-daily cigarette smokers

Abstract: Introduction Understanding factors that influence hookah use among young adults is important given its increasing popularity and health risks. The purpose of this study was to examine whether young adult non-daily cigarette smokers use hookah for stress regulation. We hypothesized that greater perceived stress and greater stressful life events would predict probability and frequency of recent hookah use. Methods Participants (n=598, 50.7% male) were non-daily smokers aged 18-24 years (M=20.5, SD=1.8), who co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Findings from a study of women experiencing homelessness indicated that those who suffered early adverse childhood experiences were more likely to meet substance use disorder (SUD) criteria in adulthood (Guillén et al., 2020). There is also a large body of evidence showing that stressful life events are associated with a higher prevalence of substance use in a variety of other populations (Allen et al., 2019, 2020; Brikmanis & Doran, 2017; Desalu et al., 2019; Parker et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Findings from a study of women experiencing homelessness indicated that those who suffered early adverse childhood experiences were more likely to meet substance use disorder (SUD) criteria in adulthood (Guillén et al., 2020). There is also a large body of evidence showing that stressful life events are associated with a higher prevalence of substance use in a variety of other populations (Allen et al., 2019, 2020; Brikmanis & Doran, 2017; Desalu et al., 2019; Parker et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most tobacco-related deaths are in the developed countries, but this trend is expected to switch by 2030 when 80% of the tobacco-related deaths will be in the developing countries [2]. A study by Brikmanis and Doranb that examine the link between stress and hookah tobacco use among young adult found that there is a positive relationship between stressful situations and increase hookah use [3]. This indicated that more stress situations increase risk of unhealthy behaviors.…”
Section: Introductionmentioning
confidence: 99%